The Effect of Project-Based Management Learning Implementation on Mathematical Problem-Solving Using Standard Indonesian in Fifth Grade Elementary School - Ignatius Joko Dewanto (The International Journal of Education Management and Sociology, 2025)
This study is a quasi-experimental research aimed at describing the effect of implementing Project-Based Management Learning on mathematical problem-solving using Standard Indonesian in Grade V at SDN Neg. 1 Tigaraksa. The sample consisted of 28 fifth-grade students from SDN Neg. 1 Tigaraksa, Tangerang Regency, in the even semester of the 2021/2022 academic year, divided into two classes: VA and VB. The study was conducted over six sessions in both the experimental and control classes. Data collection techniques included student learning outcome tests through pretests and posttests, as well as observation results. Data analysis techniques consisted of descriptive analysis and inferential analysis, which included normality tests, homogeneity tests, and hypothesis testing. The collected data were analyzed using both descriptive and inferential statistical methods. The results showed that: (1) the average learning outcome score of students in the experimental class was 83.4 with a standard deviation of 7.1, and (2) the average learning outcome score of students in the control class was 70.1 with a standard deviation of 8.4. The results of inferential statistical analysis indicated that the obtained t-test (sig 2-tailed = 0.000 < 0.05) led to the rejection of H0 and acceptance of Ha, meaning that the experimental learning method was proven to be more effective than conventional learning.